(3eNJUQ JGQjN OeTb dGHf YSGcQs - (3ESeGYjd Hf eMeO LQGM Hf YHO GdgGOi GdYLdhfi GdLQGMis; (3Ydj Hf GdMSf Hf gHI Gddg GdOeTbj , CHh GdbGSe, KbI GdOjf GHf YSGcQ,J (B600 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd ahGFO GdJGQjN s
(3GdbSe GdChd efg hjSei (B: (3GdYbO GdefXhe GdaGNQ HJdNjU JGQjN GHf YSGcQs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B106s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B422 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B262 s
Keywords: (3GdJGQjNs